Desenvolvimento de um sistema de aviso para a brusone do trigo causada por Pyricularia grisea - Cardoso, Cinara Araujo de Andrade (2006)
Blast is a common disease on rice but the occurrence of epidemics in wheat may be considered a new fact in the world. The causal agent of wheat blast is the mitotic fungus Pyricularia grisea Sacc. and Magnaporthe grisea (Hebert) Barr. in its teleomorphic phase. The main disease symptoms are shown by wheat heads, which become white especially in its apical half. The objectives of the present work were to identify the wheat blast fungus, to quantify the effects of different inoculum concentrations on disease intensity in such a way to get similar disease intensity found under field conditions and, to study the effects of temperatures and wetness duration on disease intensity. Wheat blast is one of diseases of difficult control considering the high damage caused, the absence of resistant/tolerant cultivars and the low efficiency of chemical control. The development of a warning system for wheat blast based on climatic model may help to improve our knowledgement of this pathosystem opening the opportunity to develop alternative methods for disease control. In experiments conducted in growth chambers in the Plant Pathology Laboratory of Agronomy and Veterinary Medicine Faculty of Passo Fundo University, the identification of the wheat blast causal agent was made. Fungus was isolated from rachis of naturally infected. Conidia under the light microscope showed identic to the genus Pyricularia. Conidia measurements of 100 spores presented the following size 20 32.5 x 7.5 mm, with a mean of 24.83 x 7.5 mm. Koch s postulates were performed to prove the fungus pathogenicity on wheat spikes. By taking into consideration the symptoms on inoculated plants, spores morphology and size compared to literature of disease description and by the reisolation of the pathogen it may be confirmed that the fungus used in the work is Pyricularia grisea. The goal was to get under controlled conditions a similar disease intensity as found under natural field conditions. In one trial the following conidia concentrations were tested 0, 10,000, 20,000, 30,000, 40,000, 50,000 and 60,000 spores.mL-1. In a second experiment the concentrations of 0, 5,000, 10,000, 15,000, 20,000, 25,000, 30.000 and 35,000 conidia.mL-1 were tested. In each treatment 25 heads of wheat cultivar BR 23, blast susceptible, were inoculated with a hand sprayer up to run-off. After inoculation on wheat spikes at anthesis, plants were kept under continuous wetness for 48 hours and at the temperature of 25 ± 2ºC and photoperiod of 12 hours. Disease intensity was evaluated on 15 and 30 days after inoculation. It was demonstrated that the concentration of 30,000 conidia.mL-1 is able to cause a disease intensity similar found under natural field infection and which may be used in future work. The combinations between temperature and head wetting period were assessed. Temperature range of 10, 15, 20, 25, 30 e 35 ºC and wetting periods of 0, 5, 10, 15, 20, 25, 30, 35 and 40 hours were evaluated. Each temperature formed an experiment and the hours of wetness duration the treatments. The lower disease intensity was observed at 25 °C with 10 hours of head wetness. Under wetting periods less than 10 hours of duration disease symptoms were not noticed regardless of the temperature. At the temperature of 30 °C the higher disease intensity was observed and with its increase as the wetting period increased too. Disease intensity higher than 85% was detected at 25 °C with 40 hours of wetness. Variations in blast intensity by temperature were explained by the generalized Beta model and the heads wetness duration by the Gompertz model. Disease intensity was modeled as a function of both temperature and wetness duration. The resulting equation provided a precise description of the response of Pyricularia grisea to temperature and wetness duration. The model was used to construct tables that can be used to forecast the infection based on field recorded wetness duration and temperature during this period